Unbalanced distributed and balanced concentrated winding comparison in servo motor applications - Mese, Erkan; Yasa, Yusuf; Ertugrul, Baris T.; Sincar, Eyup (ELSEVIER SCIENCE SA, 2018)
A comparison between unbalanced distributed winding and balanced concentrated winding is presented in this paper. The application is a torque motor where low speed and high torque are main requirements. Concentrated winding slot/pole combination is selected so that winding factor is maximum and as well as it is equal to the winding factor of the unbalanced winding motor. Stator and rotor Magneto-Motive Force (MMF) functions are obtained for both motor types to model torque ripple components in the frequency spectrum. Finite element analysis (FEA) and experimental results are presented to compare back EMF waveforms, magnetic loading, torque constant and thermal performance of two motors. Two designs have identical stator outer diameter (OD) and active axial length. The detailed comparison shows that two motors have similar torque constant. The behavior of two motors under heavy load differs and concentrated winding design performs better. Thermal performance of the designs is also compared and it is observed that concentrated winding design has also less winding temperature rise. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Concentrated winding; Direct drive motor; Magnetic saturation; MMF harmonics; Permanent magnet synchronous motor; Torque motor; Torque constant; Unbalanced winding; PERMANENT-MAGNET MACHINES; TORQUE-RIPPLE; DESIGN CONSIDERATIONS; SYNCHRONOUS MACHINES; Engineering